World Economy and East-West trade - The vienna institute for comparative economic studies; Nemschak, F. (New York : Springer-Verlag, 1977)
This study is a series of working sessions spread over several years, the numerous problems of economic relations between East and West.
Volume 1.
Includes bibliographical references
hza 30/01/2019
Loans
Keywords: Economic systems